Worldwide Esophageal Cancer Collaboration: neoadjuvant pathologic staging data. Issue 7 (October 2016) - Rice, T. W.; Lerut, T. E. M. R.; Orringer, M. B.; Chen, L.‐Q.; Hofstetter, W. L.; Smithers, B. M.; Rusch, V. W.; van Lanschot, J.; Chen, K. N.; Davies, A. R.; D'Journo, X. B.; Kesler, K. A.; et al.
SUMMARY: To address uncertainty of whether pathologic stage groupings after neoadjuvant therapy (ypTNM) for esophageal cancer share prognostic implications with pathologic groupings after esophagectomy alone (pTNM), we report data—simple descriptions of patient characteristics, cancer categories, and non–risk‐adjusted survival—for pathologically staged cancers after neoadjuvant therapy from the Worldwide Esophageal Cancer Collaboration (WECC). Thirty‐three institutions from six continents submitted data using variables with standard definitions: demographics, comorbidities, clinical cancer categories, and all‐cause mortality from first management decision. Of 7, 773 pathologically staged neoadjuvant patients, 2, 045 had squamous cell carcinoma, 5, 686 adenocarcinoma, 31 adenosquamous carcinoma, and 11 undifferentiated carcinoma. Patients were older (61 years) men (83%) with normal (40%) or overweight (35%) body mass index, 0‐1 Eastern Cooperative Oncology Group performance status (96%), and a history of smoking (69%). Cancers were ypT0 (20%), ypT1 (13%), ypT2 (18%), ypT3 (44%), ypN0 (55%), ypM0 (94%), and G2‐G3 (72%); most involved the distal esophagus (80%). Non–risk‐adjusted survival for yp categories was unequally depressed, more for earlier categories than later, compared with equivalent categories from prior WECC data for esophagectomy‐alone patients. Thus, survival of patients with ypT0‐2N0M0 cancers was intermediate and similar regardless of ypT; survival for ypN+ cancers was poor. Because prognoses for ypTNM and pTNM categories are dissimilar, prognostication should be based on separate ypTNM categories and groupings. These data will be the basis for the 8th edition cancer staging manuals following risk adjustment for patient, cancer, and treatment characteristics and should direct 9th edition data collection.